(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Perinatal asphyxia (PA) is a significant cause of neonatal morbidity and mortality, and may cause multi-organ dysfunction, including liver injury. Hepatic dysfunction, which is indicated by an increase in liver enzymes, is common in neonates with PA but poorly researched. Objective: The importance of hepatic dysfunction in neonates with perinatal asphyxia and its relation to the degree of asphyxia. Methods: The study was descriptive cross-sectional research whose sample consisted of the Department of Pediatric Medicine and Allama Iqbal Teaching Hospital, Dera Ghazi Khan in the duration from 13th February, 2024 to 13th August, 2024. One hundred and fifty neonates with perinatal asphyxia were involved. Liver enzymes (ALT, AST, and LDH) were detected, and the intensity of asphyxia was determined according to the Levene scale. Results: The researchers have discovered that the levels of ALT, AST, and LDH were significantly increased with the severity of PA, and peak levels were observed in severe cases. In severe PA, hepatic dysfunction was more common. Conclusion: The severity of perinatal asphyxia is closely linked to hepatic dysfunctions, and liver enzyme levels could be used as early warning signs in measuring the severity of asphyxia and to inform intervention.